Être femme et écrire en langue minorée : la double marge - Jean-François Courouau; Cécile Noilhan (Revue des Langues Romanes)
Histories and anthologies of Occitan literature tend to give women authors only a secondary place, or even to make them invisible. However, since the second half of the 19th century, many women have been involved in the renaissantiste cultural movement, particularly in literature. Several successive moments can be identified : the time of the pioneers, just before or in the wake of the Félibrige (1840-1890), was followed by a gradual emancipation (1890-1950) around powerful figures (Philadelphe de Gerde, Farfantello, Clardeluno...). The 1960s and 1970s corresponded to a phase of intense militant activity, and since the 1980s we have witnessed a normalisation of literary writing in Occitan by women. Evolving in a very masculine universe, these often forgotten women authors of Oc occupy a double margin, linguistic and gendered.